Chemically-Induced Colitis Models in Animal - R. A. Siregar; T. Widyawati; Betty (Sumatera Medical Journal, 2021)
Ulcerative colitis is a chronic inflammation that can affect the distal part of the colon, submucosa and rectal mucosa, and can affect the entire colon even to the terminal ileum. There are several factors that can cause this disease, such as genetics, environment, intestinal microbiota and the presence of enteric infectious agents. Chemical induction in experimental animals for research on gastrointestinal inflammation has been frequently used due to the similarity of the anatomical and physiological structures of experimental animals with the human digestive tract. This review focuses on recent understanding of the chemicals that used as induction agents in animals